Application of Long Non-coding RNAs in Gastric Cancer - Sang Kil Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastric cancer remains a big problem in terms of incidence or mortality; various mechanisms to explain its development and progression have been studied. Recently, long non-coding RNAs (lncRNAs) have been spotlighted in the epigenetic mechanism of cancer development. Although lncRNAs have been consistently reported to be involved in the development and progression of various cancers, there is still a lot more to be studied about them. In this article, we would like to introduce lncRNAs related to gastric cancer in order to encourage gastroenterologists to study them.